Competing Identity and Culture: The Formation of Forum Lingkar Pena and Komunitas Matapena in Indonesia - Ismah, Nor (IAIN Surakarta, 2019)
This study focusses on the genealogy of the Forum Lingkar Pena and Komunitas Matapena movements, which have produced novel Islam remaja (Islamic youth novels) and novel pop pesantren (pesantren popular novels). Using Bourdieuâ€™s concept of habitus, I analyze the field where Forum Lingkar Pena and Komunitas Matapena discourses are disseminated, particularly among Muslim youth in Indonesia and how Islamic popular culture is represented through these novels and the dynamic of youth Muslimsâ€™ community struggle for meaning in the Indonesian literary field in general. This research found that establishment of FLP and Komunitas Matapena can be described through three main ideas. Firstly, these communities encountered the massiveness of popular culture by offering a medium that supports identity formation for Muslim youth. Secondly, there is a link between the idealism promoted by Muslim organization movements and the establishment of FLP and Komunitas Matapena, and this link determines their forms and cultural products. Thirdly, they use popular culture, such as magazines and popular novels, as media to spread and preserve their idealism, targeting young people.Â Keyword: Islamic youth, FLP, habitus, popular culture, identity